Diagnostic value of microRNA-25 in patients with non-small cell lung cancer in Chinese population: A systematic review and meta-analysis. Issue 51 (18th December 2020) - Li, Chang; Sun, Lin; Zhou, Hongbin; Yang, Ying; Wang, Yong; She, Min; Chen, Jianguo
Abstract: Objective: Previous studies have shown that microRNA-25 (miR-25) plays a key role in the occurrence and development of non-small cell lung cancer (NSCLC). Many studies have shown that there is a significant increment of miR-25 in circulating blood of patients with NSCLC. The meta-analysis aims to explore diagnostic value of miR-25 in NSCLC in Chinese population. Methods: PubMed, Web of science, Excerpta Medica Database, China national knowledge infrastructure and China Wanfang database were searched to collect studies upon correlation between miR-25 and diagnosis of the patients with NSCLC until April 2020. Combined sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio and area under receiver operating characteristic curve were calculated by Stata 15.0 software. Literature assessment was conducted according to quality assessment of diagnostic accuracy studies, and documents with scores above or equal to 11 were included in this meta-analysis. Results: Six studies were included, including 480 cases with NSCLC and 451 healthy controls. The combined sensitivity (0.75, 95% confidence interval [CI]: 0.69∼0.80), specificity (0.81, 95% CI: 0.76∼0.86), positive likelihood ratio (4.04, 95% CI: 3.14∼5.20), negative likelihood ratio (0.31, 95% CI: 0.25∼0.37), diagnostic odds ratio (13.09, 95% CI: 9.37∼18.29) and area under curve (0.85, 95% CI: 0.82∼0.88) indicated that miR-25 had desirable diagnostic accuracy for NSCLC. Conclusion: MiR-25 can be applied in diagnosis of NSCLC and has potential of becoming a biomarker for detection of patients with early NSCLC in Chinese population. Abstract : Supplemental Digital Content is available in the text